The Impact of Public Speaking and Content Creator Workshops on the Digitalization of UMKM in Banyuanyar Village Boyolali - Baqiuddin; Theresia Abigail Tatontos; Tsabita Maydilla; Dhiyaulhaq Hibatullah; Jiyanto; Ardi Alvarizi (Journal of Interdisciplinary Social Sciences and Humanities, 2026)
Digitalization is the main key to increasing the competitiveness of Micro, Small, and Medium Enterprises (MSMEs), especially in rural areas such as Banyuanyar Village, Boyolali. This study aims to analyze the influence of public speaking workshops and content creator training on the development of MSME digitalization. This workshop was held as a form of empowerment of MSME actors in improving their communication skills and skills in creating digital content for onlineproduct promotion. The method used was a qualitative approach with field observation, in-depth interviews, and documentation during the activity. The results showed that MSME actors who attended the workshop experienced a significant increase in self-confidence when presenting their products and were more active in utilizing social media as a marketing tool. In addition, content creator training encouraged business actors to be more innovative in presenting their products through high-quality videos and photos. Thus, this activity has a positive impact in supporting the digital transformation of local MSMEs. This study suggests the need for the continuation of similar training and long-term mentoring so that the results achieved can continue to develop and have a broad impact.